VD_FINDINFO Faillite / 2013 / 13 vom 10. Juli 2013 - VD Tribunal cantonal (2013)
FAILLITE SANS POURSUITE PRÉALABLE, OUVERTURE DE LA FAILLITE, CALCUL DU DÉLAI, DÉLAI LÉGAL, OBSERVATION DU DÉLAI | 174 LP